Post 16 English and maths skills – 20 years ago, the Moser report was going to solve the Post 16 English and maths problem: what impact has Moser had? - Brueton, Sharon (2021)
This thesis is looking at The Moser report – ‘A Fresh Start, Improving Literacy and Numeracy’. This report, written in 1999 was a major report commissioned by government to highlight the quality of the English and maths skills of adults in England. The report provided a range of recommendations, such as a skilled teaching workforce, a new curriculum, qualification standards and a new range of transferable qualifications, many of which were implemented. Skills for Life became a new curriculum area developed directly as a result of Moser. Twelve years later, Professor Alison Wolf published The Wolf Report – ‘A Review of Vocational Education’. The Wolf Report looked again at the English and maths skills of adults in England and made further recommendations, the main one being that all students should achieve a GCSE grade A* - C in English and maths. She stated that if they have not achieved this at school, then they would need to retake these qualifications alongside their vocational or academic programme within Post 16 education. The thesis looks at the impact of the Moser report over the last twenty years, what has happened to Post 16 English and maths as a result of Moser and where we are now with English and maths skills as we celebrate the 20thanniversary of the Moser Report. What has become apparent during this thesis is that the Moser recommendations from 1999 were accepted and implemented. Twelve years later Professor Wolf’s recommendations were also accepted and implemented. Both Moser and Wolf were intended to dramatically change the English and maths skills of adults in England. 2015 onwards however, is a very different story, where very little has continued to be carried out in the way of moving Moser forward and ultimately, twenty years later, although we now have standardised qualifications, curriculums and qualified teachers, we still have millions of people in England with poor English and maths skills.